The Effects of System Quality, Information Quality, and Service Quality on the Net Benefits of the Satu Data Ketenagakerjaan Portal: The Mediating Role of User Satisfaction - Rina Irania Aminarsih; Gandung Triyono (Dinasti International Journal of Digital Business Management, 2026)
Digital transformation in public administration requires reliable, informative, and responsive public data services that deliver tangible benefits to users. However, no empirical study has specifically examined the application of the DeLone and McLean Information Systems Success Model to Portal Satu Data Ketenagakerjaan as an integrated government public data service in the labor sector. This study examines the effects of System Quality, Information Quality, and Service Quality on User Satisfaction and Net Benefits of Portal Satu Data Ketenagakerjaan and tests the mediating role of User Satisfaction. A quantitative explanatory approach was used, with data collected through an online questionnaire from 100 portal users selected by purposive sampling during May-June 2026. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS version 4.1.1.8. The results show that System Quality, Information Quality, and Service Quality positively and significantly affect User Satisfaction and Net Benefits. User Satisfaction also positively and significantly affects Net Benefits and mediates the effects of all three quality dimensions through complementary partial mediation. The novelty lies in applying the DeLone and McLean Information Systems Success Model to Portal Satu Data Ketenagakerjaan as an integrated government public data service supporting Satu Data Indonesia in the labor sector, while examining User Satisfaction as a mediating mechanism in generating Net Benefits